Responsive web design system for student representative council based on Shneiderman’s Eight Golden Rules / Muhammad Muadzzim Muhammad Jizan - Muhammad Jizan, Muhammad Muadzzim (2017)
SRC of UiTM Malacca Branch Jasin Campus found out there are problems with the the uncertainty of platform to convey/receive information around campus, difficulty to get information about calendar of student activities and unclear platform to voice out ideas and problems. Nowadays, lots of communication media created by IT developer for public. Students of UiTM Malacca facing problem when they organize an event and hard for them to blast the information to all students in campus. SRC as the highest student organization in university take an initiative to have an official website to centralize the medium of communication among UiTM Malacca Branch Jasin Campus students. The aim is to develop a responsive web design based on Shneiderman’s Eight Golden Rules. It consist of eight rules that focus on design principles to ensure the system not become a frustration for the interface. At the end of the development, this system will be used by students of UiTM Malacca Branch Jasin Campus which consist of around 4000 and that give strong motivation to make sure this system is completed within time. For assistance of the development, this system was guided by using System Development Life Cycle (SDLC) methodology which modified into 4 phases. The phases are analysis, design, develop and testing. At the end of the development, the system scores 4.62 on the usefulness, 4.21 on the ease of use, 4.64 on the ease of learning and 4.69 on the satisfaction out of 5 marks when usability testing was conducted among 13 participants. In future, this system will be upgrade to cater the students of whole UiTM Malacca which have amount of around 13000 and will be implement at each UiTM in every state of Malaysia.